The Impact of Climate change on the Asian Century and Vice Versa - Tshering, Leki (Kathmandu School of Law Review, 2019)
There are various threats to Asia in realizing its potential to achieve the Asian century, among which climate change is the most prominent. Climate change, which was once considered to be a human constructed myth, is no longer a myth. Rather it is a hard reality for everyone. The devastating impact of climate change is being and will have to be borne by every state irrespective of the degree of intensity and the frequency of contribution made by them. With the advancement in the economic status of the Asian countries, there will be a lot of pressure on the natural resources and if the current trend of using non-renewable resources continues then the impacts of climate change will be more apparent not so far from now. We are already facing the effects of climate change which were mainly caused by the development of other continents. This article seeks to demonstrate how climate change is going to affect Asia with the change in time and simultaneously also tries to provide feasible measures to tackle it. This paper also attempts to identify the various sectors which require immediate attention so as to tackle climate change by reforming them. This paper will also illustrate an overview of what we can learn from the 19th and the 20th century which were considered as the European century and the American century respectively. It will also shed light on how Asian century can be different from the previous two centuries. This paper, in conclusion, will discuss how sustainable development can play a role in tackling climate change and how we can bring in multilateral cooperation among the Asian states to tackle climate change and ultimately place everyone in a better position.